Summary of 1991 Supreme Court rulings, January to June 1991 - Martinez, Daniel T. (Central Book Supply, Inc., 1992)
Part I : Political law -- Labor and social legislation -- Civil law -- Taxation -- Mercantile law -- Criminal law.